Augmented Reality Application - Hendri Yawan (EDUTEC : Journal of Education And Technology, 2022)
This article aims to investigate the studies about the implementation Augmented Reality (AR) in Education, particularly to have a closer look at the opportunities and challenges of AR application in Indonesian educational context. Finding of this study were analyzed through a synthesis research. The current empirical studies related to AR implementation in education were descriptively analyzed, and carefully synthesized. AR is one of the emerging technologies which has a big promise on teaching and learning. This study reveals that AR may offer a meaningful and engaging learning experiences because AR based learning can provide critical thinking activity with problem solving tasks. Furthermore, well-designed AR may situate a collaborative learning which can enhance students’ positive behavior and attitude. However, this essay also reveals some limitations of AR application need to be taken into consideration, especially when it comes to technological and learning issues. Consequently, AR may not be the ideal solution for all learning settings, yet the ongoing development of AR technology on handheld mobile devices offers a big optimism for future learning. It is highly expected that the vast development of AR may positively influence learning and become more significant in the future.